Temporal variation in plant-soil feedback controls succession - Kardol, Paul; Martijn Bezemer, T; Putten, Wim H. van der (Ecology letters, 2006)
Soil abiotic and biotic factors play key roles in plant community dynamics. However, little is known about how soil biota influence vegetation changes over time. Here, we show that the effects of soil organisms may depend on both the successional development of ecosystems and on the successional position of the plants involved. In model systems of plants and soils from different successional stages, we observed negative plant-soil feedback for early-successional plant species, neutral feedback for mid-successional species, and positive feedback for late-successional species. The negative feedback of early-successional plants was independent of soil origin, while late-successional plants performed best in late- and worst in early-successional soil. Increased performance of the subordinate, late-successional plants resulted in enhanced plant community diversity. Observed feedback effects were more related to soil biota than to abiotic conditions. Our results show that temporal variations in plant-soil interactions profoundly contribute to plant community assemblage and ecosystem development.